Manajemen Kesiswaan Semi Pesantren di Sekolah Dasar Islam - Daratista, Iin; Sufirmansyah, Sufirmansyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research focuses on student management in realizing effective and efficient educational governance at SDI Darul Qur'an (Prioritas Tahfidz) Kanigoro - Kras - Kediri. All components in this institution must be managed properly, including students. The student management adopted by this institution is a program of semi-islamic boarding school activities. Starting from the student recruitment process which does prioritize the student readiness factor. The process of learning activities is supported by qualified educators in accordance with their respective fields. The whole series of activity programs has the aim of being able to equip students to be independent and skilled in life in the future because they have experienced the learning process in this institution. This research uses qualitative methods with a descriptive qualitative approach, as well as with data collection techniques through interviews. Through the process of analysis of the entire series of semi-islamic activity programs shows that students can have multidisciplinary abilities. It is proven from positive attitudes and behavior patterns as well as students' critical thinking methods and are able to apply their knowledge at school and in the community through habituation of activities at school every day.